2013
DOI: 10.1039/c2ay26128f
|View full text |Cite
|
Sign up to set email alerts
|

Detection of concanavalin A based on attenuated fluorescence resonance energy transfer between quantum dots and mannose-stabilized gold nanoparticles

Abstract: Highly sensitive biosensing of concanavalin A (Con A) has been developed based on the attenuation of FRET efficiency between amine-terminated quantum dots and mannose-stabilized Au nanoparticles in the presence of Con A, which inhibits the H-bonding formation of the QDs-AuNPs assembly, thereby causing the fluorescence recovery.Scheme 1 Schematic illustration of (A) FRET between amine-terminated QDs and mannose-stabilized AuNPs, and (B) Con A-induced attenuation of FRET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…In Tris buffer, K sv was determined to be 6.38 × 10 7 M −1 (F 0 /F = 1.037 + 0.054 [AuNPs], r 2 = 0.999). This constant is quite similar to that obtained with mannose-stabilized AuNPs in our previous report [29]. This experimental result clearly indicates that the fluorescence emission of CdTe QDs is quenched by the galactose-stabilized AuNPs.…”
Section: Fret Between Qds and Aunpssupporting
confidence: 89%
See 3 more Smart Citations
“…In Tris buffer, K sv was determined to be 6.38 × 10 7 M −1 (F 0 /F = 1.037 + 0.054 [AuNPs], r 2 = 0.999). This constant is quite similar to that obtained with mannose-stabilized AuNPs in our previous report [29]. This experimental result clearly indicates that the fluorescence emission of CdTe QDs is quenched by the galactose-stabilized AuNPs.…”
Section: Fret Between Qds and Aunpssupporting
confidence: 89%
“…In our previous work, we have shown that the hydrogen bonding between the amine groups of QDs surfaces and the hydroxyl groups of the α-mannose-stabilized on the AuNPs leads to the formation of AuNPs-QDs assembly [29]. In the present work, the identical hydrogen bonding formation was observed with β-galactose-stabilized AuNPs.…”
Section: Fret Between Qds and Aunpssupporting
confidence: 72%
See 2 more Smart Citations
“…[22][23][24][25][26][27] It is well known that concanavalin A is a legume lectin from Jack beans containing four identical binding sites. Each monomer subunit of Con A is approximately 4 Â 4 Â 4 nm with a single small binding site capable of binding to a-D-glucopyranose with unmodified hydroxy groups at positions C3, C4 and C6.…”
Section: Introductionmentioning
confidence: 99%